2018
DOI: 10.1097/spc.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Compassion in palliative care: a review

Abstract: Purpose of review Compassion has been recognized as a key aspect of high-quality healthcare, particularly in palliative care. This article provides a general review of the current understanding of compassion in palliative care and summarizes emergent compassionate initiatives in palliative care at three interdependent levels: compassion for patients, compassion in healthcare professionals, and compassionate communities at the end of life. Recent findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 66 publications
0
39
0
7
Order By: Relevance
“…Compassionate care was chosen as the theoretical framework (Blomberg et al, 2016; Brito‐Pons & Librada‐Flores, 2018; Crawford et al, 2014; Robinson et al, 2019). This framework had an impact on how the data were collected and interpreted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compassionate care was chosen as the theoretical framework (Blomberg et al, 2016; Brito‐Pons & Librada‐Flores, 2018; Crawford et al, 2014; Robinson et al, 2019). This framework had an impact on how the data were collected and interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Compassion is fundamental to palliative care and can create an environment of safety for patients and family caregivers. Compassionate care is built on trust and good relationships between the patient, the family and healthcare personnel (Brito‐Pons & Librada‐Flores, 2018; Larkin, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comprehensive review defined compassion in palliative care as a "a complex and multifacted response to suffering" involving, "sensitivity, recognition, understanding, emotional resonance, empathic concern, and distress tolerance for another's pain or suffering, coupled with a motivation, and relational action to ameiolorate it." [13] A grounded theory study of the perspectives of patients with advanced cancer regarding the differences between empathy, sympathy and compassion found that patients associated compassion with themes of being motivated by love; expressing an altruistic response; being action-oriented; and expressing a form of supererogatory kindness. Echoing the earlier commentary on the ambivalence of sympathy, patients considered it to be largely unhelpful, especially when compared to empathy and compassion which were viewed positively by patients, with most preferring compassion's orientation toward action-and virtue-based motivators.…”
Section: Compassion In End-of-life Carementioning
confidence: 99%
“…Compassion may be nursing's most vital and precious asset (Burnell, ; Cornwell, Donaldson, & Smith, ), but is poorly defined in current nursing literature (Adamson & Dewar, ; Dewar, Adamson, Smith, Surfleet, & King, ; Kenny, ; McCaffrey & McConnell, ). Still, compassion has recently emerged as a growing topic of interest in nursing literature (Bramley & Matiti, ; Brito‐Pons & Librada‐Flores, ; Department of Health & NHS Commissioning Board, ; McCaffrey & McConnell, ; Sinclair et al, ; Sinclair, McClement, et al, ; Sinclair, Norris, et al, ; Zamanzadeh, Valizadeh, Rahmani, Cingel, & Ghafourifard, ).…”
Section: Introductionmentioning
confidence: 99%